2014
DOI: 10.3389/fgene.2014.00262
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the glycogenome of schistosomes

Abstract: Schistosoma mansoni and other Schistosoma sp. are multicellular parasitic helminths (worms) that infect humans and mammals worldwide. Infection by these parasites, which results in developmental maturation and sexual differentiation of the worms over a period of 5–6 weeks, induces antibodies to glycan antigens expressed in surface and secreted glycoproteins and glycolipids. There is growing interest in defining these unusual parasite-synthesized glycan antigens and using them to understand immune responses, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 169 publications
(303 reference statements)
0
26
0
Order By: Relevance
“…Glycosylation in schistosomes is a complex process which plays an essential role in host-pathogen interplay, particularly in terms of immune evasion and modulation [ 82 ]. A comprehensive glycomic analysis has revealed that the dominant N-glycans structure dynamically changes during the development of S mansoni .…”
Section: Resultsmentioning
confidence: 99%
“…Glycosylation in schistosomes is a complex process which plays an essential role in host-pathogen interplay, particularly in terms of immune evasion and modulation [ 82 ]. A comprehensive glycomic analysis has revealed that the dominant N-glycans structure dynamically changes during the development of S mansoni .…”
Section: Resultsmentioning
confidence: 99%
“…The double mutant population increased very slowly in both A/JCr and C57BL/6 mice, likely due to its slower growth rate under stress ( Fig 6C , S4 Fig ) and reduced ability to resist host defenses ( Fig 6A and 6B ). Xyl modifications have been identified as immunodominant epitopes in antibody responses to allergens and pathogens [ 39 , 40 ], and the absence of Xyl modifications in uxt1 Δ uxt2 Δ did increase immune detection and clearance of the pathogen in vitro ( Fig 6A and 6B ). The mutant also remained confined to the lungs of A/JCr mice ( S7 Fig ) and was slow to cause lethal meningoencephalitis in C57BL/6 mice ( S6 Fig ).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been indicated that tick-derived carbohydrates (such as alpha fucosylation of tick glycoproteins by fucosyltransferases) are role-players in tick-pathogen interactions, such as colonization and transmission in vector cells (e.g., Anaplasma phagocytophilum ) (de La Fuente et al, 2006 ; Pedra et al, 2010 ; Cabezas-Cruz et al, 2017 ). Similar studies in schistosomes have indicated an important role of glycan epitopes in host-parasite interactions including modulation and evasion of host innate and adaptive immunity, as well as infection biology during snail-schistosome interactions (e.g., fucosylated structures produced on larval surfaces and released during larval transformation and sporocyst development) (Mickum et al, 2014 ; Jurberg and Brindley, 2015 ; Smit et al, 2015 ; Nascimento Santos et al, 2017 ). Investigation of carbohydrate-protein interactions have been revolutionized with the development of functional glycomics tools such as glycan arrays that have been applied successfully in the analysis of glycan binding protein associated biology, host-pathogen interactions and immune recognition (by antigen specific antibodies) (Heimburg-Molinaro et al, 2011 ; Rillahan and Paulson, 2011 ; Arthur et al, 2014 ).…”
Section: Metazoan Vaccine Development: Identification To Formulationmentioning
confidence: 83%